Ocular complications and loss of vision due to herpes zoster ophthalmicus in patients with HIV infection and a comparison with HIV-negative patients. (February 2013) - Nithyanandam, S; Joseph, M; Stephen, J
The aim of the work is to describe the occurrence of ocular complications and loss of vision due to herpes zoster ophthalmicus (HZO) in HIV-positive patients who received early antiviral therapy for HZO. This is a post hoc analysis of prospectively collected data. Twenty-four HIV-positive patients with HZO were included in this report; male to female ratio was 3.8:1; mean age was 33.5 (±14.9) years. The visual outcome was good, with 14/24 patients having 6/6 vision; severe vision loss (≤6/60) occurred in only 2/24. There was no statistical difference in the visual outcome between the HIV-positive and -negative patients ( P = 0.69), although severe vision loss was more likely in HIV-infected patients. The ocular complications of HZO in HIV-infected patients were: reduced corneal sensation (17/24), corneal epithelial lesions (14/24), uveitis (12/24), elevated intraocular pressure (10/24) and extra-ocular muscle palsy (3/24). The severity of rash was similar in the two groups but multidermatomal rash occurred only in HIV-infected patients (4/24). There was no difference in the occurrence of ocular complications of HZO between HIV-positive and HIV-negative patients. HZO associated ocular complications and visual loss is low in HIV-infected patients if treated with HZO antiviral therapy and was comparable with HIV-negative patients. Early institution of HZO antiviral therapy is recommended to reduce ocular complication and vision loss.